The imact of crop rotation and fertilisation on the SPAD values of winter wheat on chernozem soil in a long-term experiment - Szilágyi, Gergely (Acta Agraria Debreceniensis, 2014)
We have carried out our outdoor field experiments at the Látókép Experimental Farm of the CAS of the University of Debrecen in the cropyear of 2012/2013 on chernozem soil in a long-term experiment. We have studied the effects of two different preceding crops (sweet corn, sunflower) on the development of the SPAD values of wheat varieties of different genotypes in the cases of control, N60+PK and N120+PK fertilizer treatments. According to our research results, we have concluded that the preceding crop, the fertilizer application and the variety selection influenced the SPAD values. According to our data, we have measured higher SPAD values after sweet corn preceding crop, the standard deviations were in a smaller range in the case of the studied varieties. After sunflower preceding crop, smaller averages were experienced with wider standard deviation range. In the case of favourable preceding crop, the differences between the varieties are more pronounced than in the case of unfavourable preceding crop. The maximal SPAD values were measured in milky ripening in the case of N120+PK fertilizer treatment.